From Pesantren to the Public Stage: Divergence of Approaches to Quranic Interpretation between Kiai and Celebrity Preachers: Dari Pesantren ke Panggung Publik: Divergensi Pendekatan Tafsir Al-Qur’an antara Kiai dan Pendakwah Selebriti - Fawaid, Ahmad; Maulidin, Ahmad (Takwil: Journal of Quran and Hadith Studies, 2025)
The divergence in Qur'anic interpretive approaches between traditional Islamic boarding school clerics (kiai) and celebrity preachers is increasingly evident on social media, where diverse styles and methods of da'wah converge. This study conducts a comparative analysis of interpretive approaches, focusing specifically on Surah al-Insyirah, as presented by two prominent figures: Gus Baha’, representing the traditional pesantren scholar, and Ustadz Adi Hidayat, as a representative of the celebrity preacher. Employing a qualitative descriptive method with a comparative study approach, data were collected through unobtrusive observation of texts, manuscripts, videos, and recorded tafsir sessions shared on social media platforms. The data were analyzed using Thomas Kuhn’s paradigm shift framework. The findings indicate that in addition to linguistic elements, the distinguishing features of Adi Hidayat’s approach include psychological and sociological dimensions, which lead to notable divergences in the duration, method, stages, and delivery attributes of the tafsir. These results affirm that the interpretive divergences between Gus Baha’ and Adi Hidayat are not to be viewed in opposition, but rather as complementary responses tailored to varying audience needs and levels of understanding.